The death of a family member (brother) reflected in a long dream series - Schredl, Michael (International journal of dream research, 2025)
The death of a loved one is often a very impactful event in the life of a person, and 50% to 86% of persons who experienced a significant loss reported dreaming about the deceased. The present analysis is based on a long dream series (N = 14,520 dreams), including a period of three years recorded after the unexpected death of the dreamer’s brother. The findings indicate that after the death of the brother the frequency of brother dreams decreased. Dreams in which the brother occurred as being dead were rare, more often the death of the brother is reflected in a general way. e.g., telling someone about his death, finding “old” stuff of the brother. Overall, the findings highlight the importance of collecting a series of dreams after loss as completely as possible and not focus only on the most memorable dreams people have of the deceased. Additionally, the findings indicate that many dreams of the brother seem to refer to past shared experiences and not refer to the death and/or the grief process. These types of dreams might be helpful in grief counselling as they reflect the close connection the dreamer had with the deceased.
Gesehen am 08.10.2025